FEATURES OF CHOOSING THE RIGHT LESSON PLAN - Abdurahmonova, Zebo (Журнал иностранных языков и лингвистики, 2023)
An effective lesson plan integrates these three components: objectives for student learning, teaching and learning objectives, and strategies to check student understanding. There are six steps to preparing an effective lesson plan.